Immunization Status and Challenges During COVID-19 and Associated Factors Among Children Aged 10–23 Months in South Region, Ethiopia 2020 - Wale Tegegne A; Kassie Gidafie A; Girma Mamo Snr D; Tilahun Wassie S; Abita Mengie Z (Dove Medical Press, 2021)
Alemnew Wale Tegegne,1 Aychew Kassie Gidafie,2 Desalegn Girma Mamo Snr,1 Semahegn Tilahun Wassie,1 Zinie Abita Mengie1 1Department of Midwifery, College of Medicine and Health Science, Mizan Tepi University, Tepi, Ethiopia; 2Department of Nursing, College of Medicine and Health Science, Mizan Tepi University, Tepi, EthiopiaCorrespondence: Alemnew Wale Tegegne Tel +251918657367Email walealemnew@gmail.comBackground: The worldwide COVID-19 pandemic is overstressing health systems and Essential health services and vaccination services are disrupted. Immunization is a confirmed gizmo for governing and even eliminating communicable diseases.Objective: This study aims to assess the challenge and status of immunization during COVID-19 and associated factors among children aged 10– 23 months south Nation Nationality and People Region Ethiopia. Methods and Materials: community-based mixed quantitative and qualitative cross-sectional study was done in southwest Ethiopia. Data was collected using semi-structured questionnaires and in-depth interviews. After that, the data were edited, coded, and move in into Epi info version 7.2 for data management then transported to SPSS version 25 for analysis. The analyzed data were presented by tables, graphs, figures, and text form.Results: According to this study, the prevalence of incomplete immunization was found to be 809 (62.2%) with (95% CI: 59.5, 64.8). In multivariable analysis waiting time at a health facility (AOR=0.04, 95% CI 0.0001,0.004), education (AOR=5.08,95% CI2.31,11.14), place of delivery (AOR=2.34,95% CI 4.96,6.089), fearing of COVID-19 (AOR=3.62,95% CI 1.72,7.64) and do not understand the separation care of COVID-19 and other health services (AOR=2.85,95% CI1.38,5.9) were significantly associated factors.Conclusion: The prevalence of incomplete immunization among children aged 10– 23 months was very high in this study as compared to the other studies done in a different pocket of Ethiopia. Consecutively, reducing waiting time at a health facility, avoiding unnecessary fear of COVID-19, and promoting immunization in a different area of southwest Ethiopia along with health extension workers are recommended.Keywords: immunization status, challenge, children 12– 23-month-old, southwest Ethiopia